(3GdeOhfIs - (3CHh YHO Gddg YHO GdQMef GHf GdbGSe GdeGdcj,J (B191 (3g` s ((3CMeO YeQ s)
(3ChdgG (B:s
(3HGH GdYJb s
(3BNQgG (B:s
(3dh cGf MjkG aCOi Yf CNjg s
(3cJGHG GdYJbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1644s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs